Rethinking Securities in an Emergent Technoscientific New World Order : Retracing the Contours for Africa's Hi-jacked Futures - Nhemachena, Artwell; Mawere, Munyaradzi (Langaa Research & Publishing CIG, 2018)
The emergent technoscientific New World Order is being legitimised through discourses on openness and inclusivity. The paradox is that openness implies vulnerability and insecurities, particularly where closure would offer shelter. While some actors, including NGOs, preach openness of African societies, Africans clamour for protection, restitution and restoration. Africans struggle for ownership and access to housing, for national, cultural, religious, economic, and social belonging that would offer them the necessary security and protection, including protection from the global vicissitudes and matrices of power. In the presence of these struggles, to presuppose openness would be to celebrate vulnerability and insecurities. This book examines ways in which emergent technologies expose Africans and, more generally, peoples of the global south to political, economic, social, cultural and religious shocks occasioned by the coloniality of the global matrices of power. It notes that there is the use -- by global elites -- of technologies to incite postmodern revolutions designed to compound the vicissitudes and imponderables in the already unsettled lives of people north and south. Particularly targeted by these technologies are African and other governments that do not cooperate in the fulfilment of the interests of the hegemonic global elites. The book is handy to students and practitioners in security studies, African studies, development studies, global studies, policy studies, and political science.
Keywords: Globalization -- Africa.; Technological innovations -- Social aspects -- Africa.; Technology -- Social aspects -- Africa.; Mondialisation -- Afrique.; Innovations -- Aspect social -- Afrique.; BUSINESS & ECONOMICS / Industries / General.; SOCIAL SCIENCE / Regional Studies; Globalization; Technological innovations -- Social aspects; Technology -- Social aspects; Africa